The Role of Benzylpenicilloyl Epimers in Specific IgE Recognition - Mayorga, Cristobalina; Montañez, Maria I.; Najera, Francisco; Bogas, Gador; Fernandez, Tahía D.; Gil, David Rodríguez; Palacios, Ricardo; Torres, Maria J.; Vida, Yolanda; Perez-Inestrosa, Ezequiel (Frontiers in Pharmacology, 2021)
The high prevalence of allergy to beta-lactams is a worldwide issue. Accuracy of diagnostic methods is important to prove tolerance or allergy, with skin test considered the best validated in vivo method for diagnosing immediate reactions to beta-lactams. For these tests, the inclusion of major and minor determinants of benzylpenicillin (BP) is recommended. These metabolite concentrations will be highly dependent on their stability and relevant in the specific IgE recognition, although in a different degree. Commercial skin test reagents have changed along time, including as minor determinants benzylpenicillin, benzylpenicilloate (BPO), and benzylpenilloate (PO). Major determinants consists of multivalent conjugates of benzylpenicilloyl coupled through amide bond to a carrier polymer, such as penicilloyl-polylysine (PPL) or benzylpenicilloyl-octalysine (BP-OL). Nuclear magnetic resonance stability studies of minor determinants and Butylamine-Benzylpenicilloyl (Bu-BPO) conjugate, as a simple model for major determinants, indicated that BP, Bu-BPO, and PO are stable in aqueous solution at physiological pH. However, BPO ((5R,6R)-BPO) slowly epimerizes in its C-5 (resulting in (5S,6R)-BPO), in a pH and temperature dependent. Density Functional Theory (DFT) calculations indicate the formation of different intramolecular hydrogen bonds in PO, BPO, and Bu-BPO, in their most stable conformation, which contributes to the further stabilization of Bu-BPO in comparison with BPO and PO. Nevertheless, similar epimerization behavior was found with Bu-BPO at basic pH conditions, and (5R,6R)-Bu-BPO and (5S,6R)-Bu-BPO were selected as model for evaluating the role of the different epimers in the immunoreactivity with sera from penicillin-allergic patients. Results show that the spatial configuration of C-5 of benzylpenicilloyl determinants significantly affects IgE recognition, which may have important implications for both the reproducibility and sensitivity of in vivo and in vitro diagnostic tests.